HUBUNGAN ADEKUASI HEMODIALISIS DENGAN STATUS GIZI DAN RISIKO TERJADINYA MALNUTRI SI PADA PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS DI RUMAH SAKIT PKU MUHAMMADIYAH YOGYAKARTA - Tiffany Dyah Rinanti (FKU 16 UMY 014, 2016)
Background : Malnutrition or malnutrition is an important predictor of mortality in hemodialysis patients. An estimated 50 % -70 % of dialysis patients showed signs and symptoms of malnutrition. Markers of malnutrition affects physical domain the quality of life of patients with chronic renal failure undergoing hemodialysis. Objective : To determine the relationship between the adequacy hemodialialisis with nutritional status and risk of malnutrition in hemodialysis patients at PKU Muhammadiyah Hospital in Yogyakarta. Methods : This study is a correlative analytic cross sectional approach using a convenience sampling with 55 respondents who meet the criteria of inclusion-exclusion. Hemodialysis adequacy of the data collection is done by the formula Kt/V, measurements of body mass index (BMI) and the upper arm circumference (LLA) to assess the nutritional status and the risk of malnutrition using the screening questionnaire Nitrition Simple Screening Tool (SNST) Results and Discussion : Statistical test results between hemodialysis adequacy and nutritional status assessed by BMI indicates the value of p = 0,083 where p > 0,05. The p-value in a statistical test between hemodialysis adequacy and nutritional status was measured by the LLA money shows the value of p = 0,946 where p > 0,05 . The statistical test on the relationship between the adequacy of hemodialysis at risk of malnutrition were assessed by questionnaire SNST shows the value of p = 0,027 where p < 0,05. Conclusions : There was no relationship between hemodialysis adequacy and nutritional status assessed by BMI and LLA. There was a relationship between hemodialysis adequacy and risk of malnutrition that were assessed by questionnaire SNST